Kajian Bentuk, Fungsi Dan Makna Patung Loro Blonyo Dengan Pendekatan Estetika Seni Nusantara - Prasetyo, Raden Ersnathan Budi (Institut Seni Indoensia Surakarta, 2009)
According to historical records, the statue of Loro Blonyo has existed since the time of the leadership of Sultan Agung of Mataram Kingdom in 1476. Manifestation of Hinduism was later modified to be more universal, to the statue of the Dewi Sri to bridal pair. At first, Loro Blonyo ownership is closely related to art and culture. Only the gentry who have it. In joglo house, the statue Loro Blonyo is placed at sentong or middle part of the house. The part that is considered as a private area husband and wife. In addition, Loro Blonyo also to be Krobongan complementary. This relates to several miitos that accompanies the presence of the Statue of Loro Blonyo. Loro Blonyo Statue of traditional forms of symbolic display smoothly because it is associated with ritual functions. Once pulled, the statue of Loro Blonyo is still favored by the people, although it functions and how to interpret this statue has been changed. Symbolic display of this statue are parsed in this paper. With the nusantara aesthetic approach of this paper is expected able to dissect the meanings embodied in symbolic statue Loro BlonyoÂ Keywords: Loro Blonyo, symbolic meaning, nusantara aesthetics.